Deriving emission factors for mangrove blue carbon ecosystem in Indonesia - Murdiyarso, D.; Krisnawati, H.; Adinugroho, W.C.; Sasmito, S.D. (Springer, 2023)
Using ‘higher-tier’ emission factors in National Greenhouse Gas Inventories is essential to improve quality and accuracy when reporting carbon emissions and removals. Here we systematically reviewed 736 data across 249 sites (published 2003–2020) to derive emission factors associated with land-use change in Indonesian mangroves blue carbon ecosystems. Four management regimes—aquaculture, degraded mangrove, regenerated mangrove and undisturbed mangrove—gave mean total ecosystem carbon stocks of 579, 717, 890, and 1061 Mg C ha−1 respectively. The largest biomass carbon stocks were found in undisturbed mangrove; followed by regenerated mangrove, degraded mangrove, and aquaculture. Top 100-cm soil carbon stocks were similar across regimes, ranging between 216 and 296 Mg C ha−1. Carbon stocks between 0 and 300 cm varied significantly; the highest values were found in undisturbed mangrove (916 Mg C ha−1), followed by regenerated mangrove (803 Mg C ha−1), degraded mangrove 666 Mg C ha−1), and aquaculture (562 Mg C ha−1). Using deep layer (e.g., 300 cm) soil carbon stocks would compensate for the underestimation of surface soil carbon removed from areas where aquaculture is widely practised. From a project perspective, deep layer data could secure permanence or buffer potential leakages. From a national GHG accounting perspective, it also provides a safeguard in the MRV system.